Mirror Symmetry Coils for Foreign Object Detection and Location with Wireless Power Transmission - Xu, Yuhui; Xu, Jin (Recent Advances in Electrical & Electronic Engineering, 2025)
Background Wireless power transmission technology effectively avoids safety issues caused by accidental contact, wire aging, and friction. However, due to the presence of foreign objects, other severe accidents such as fire hazard can occur, and the charging system can be interfered with and even damaged by the foreign objects. Methods Therefore, this paper proposes (MSD) mirror symmetry detection coils to detect and locate foreign objects. First, we conduct theoretical analysis and derive formulas to validate our proposed method. Next, we employ ANSYS Maxwell to simulate the (WPT) wireless power transmission system, considering various sizes and materials of foreign objects and comparing them to a system without foreign objects. Results Furthermore, we conducted experiments using mirror symmetrical detection coils to detect and locate foreign objects, providing additional verification for our proposed method. Conclusion The simulation and experimental results show that the proposed method of mirror symmetry detection coils can effectively identify and locate the foreign objects.
Keywords: wireless power transmission